2014
DOI: 10.3390/nu6114856
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic Acid Can Attenuate Metabolic Deviations Caused by a High-Sucrose Diet without Causing Water Retention in Male Sprague-Dawley Rats

Abstract: Glycyrrhizic acid (GA) ameliorates many components of the metabolic syndrome, but its potential therapeutic use is marred by edema caused by inhibition of renal 11β-hydroxysteroid dehydrogenase 2 (11β-HSD2). We assessed whether 100 mg/kg per day GA administered orally could promote metabolic benefits without causing edema in rats fed on a high-sucrose diet. Groups of eight male rats were fed on one of three diets for 28 days: normal diet, a high-sucrose diet, or a high-sucrose diet supplemented with GA. Rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Twenty seven male Wistar rats, 100–120 g, were maintained in a controlled temperature (24–26 °C), relative humidity of 60–80% and on a 12-h light–dark cycle for one week acclimatization. Rats were randomly allocated using list randomizer ( https://www.random.org/lists ) into 3 groups with 9 rats/group as follow; Group1: served as a control, Group 2: represented diabetic rats, and Group 3: denoted as the treated group in which the diabetic rats received intraperitoneal (IP) injection of 100 mg/kg/3 times a week GA (Sigma-Aldrich, St Louis, MO, USA) for 8 weeks 33 , 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Twenty seven male Wistar rats, 100–120 g, were maintained in a controlled temperature (24–26 °C), relative humidity of 60–80% and on a 12-h light–dark cycle for one week acclimatization. Rats were randomly allocated using list randomizer ( https://www.random.org/lists ) into 3 groups with 9 rats/group as follow; Group1: served as a control, Group 2: represented diabetic rats, and Group 3: denoted as the treated group in which the diabetic rats received intraperitoneal (IP) injection of 100 mg/kg/3 times a week GA (Sigma-Aldrich, St Louis, MO, USA) for 8 weeks 33 , 34 .…”
Section: Methodsmentioning
confidence: 99%
“…Diammonium glycyrrhizinate (DG), a medicinal form of glycyrrhizic acid as well as a natural and major bioactive pentacyclic triterpenoid glycoside extracted from licorice roots, possesses comprehensive pharmacological properties such as antiviral, anti-inflammatory, antiallergic, antioxidant, and antitumor characteristics, among others. DG is commonly used as one of therapeutic agents for the treatment and control of chronic hepatopathy including NAFLD. It also has been proven to alleviate serum liver enzymes and ameliorate pathological damage of the liver because of its anti-inflammatory mechanisms of action in the liver. , Previous studies have shown that DG was mainly distributed in the liver and intestines after being absorbed into the blood . In addition, it can significantly alleviate the intestinal mucosa inflammation in mice .…”
Section: Introductionmentioning
confidence: 99%
“…According to Glavac and Kreft [12], after oral ingestion of 600 mg of glycyrrhizin in human subjects, the metabolites appear in urine ranging from 1.5 to 14 h and can be detected in the urine even after 4 days. Protection of liver cells from experimentally induced metabolic disorders and hepatocellular injury by glycyrrhizin has been reported in different publications [13][14][15][16][17][18][19]. Antidiabetic effect of glycyrrhizin and its metabolite 18b-glycyrrhetinic acid has been reported in streptozotocin-induced type 1 diabetes mellitus in rat model [20,21].…”
Section: Introductionmentioning
confidence: 99%